Three tomato genes code for heat stress transcription factors with a region of remarkable homology to the DNA-binding domain of the yeast HSF. - Scharf, K D (1990)
Heat stress (hs) treatment of cell cultures of Lycopersicon peruvianum (Lp, tomato) results in activation of preformed transcription factor(s) (HSF) binding to the heat stress consensus element (HSE). Using appropriate synthetic HSE oligonucleotides, three types of clones with potential HSE binding domains were isolated from a tomato lambda gt11 expression library by DNA-ligand screening. One of the potential HSF genes is constitutively expressed, the other two are hs-induced. Sequence comparison defines a single domain of approximately 90 amino acid residues common to all three genes and to the HSE--binding domain of the yeast HSF. The domain is flanked by proline residues and characterized by two long overlapping repeats. We speculate that the derived consensus sequence is also representative for other eukaryotic HSF and that the existence of several different HSF is not unique to plants.